Exposure to Online Hate in Four Nations: A Cross-National Consideration. Issue 3 (4th March 2017) - Hawdon, James; Oksanen, Atte; Räsänen, Pekka
ABSTRACT: There is a considerable amount of hate material online, but the degree to which individuals are exposed to these materials vary. Using samples of youth and young adults from four countries, we investigate who is exposed to hate materials. We find support for using routine activity theory to understand exposure at the individual level; however, there is significant cross-national variation in exposure after accounting for individual-level factors. We consider two plausible hypotheses that could account for this cross-national variation. The data best fit the hypothesis that anti–hate speech laws may provide a source of guardianship against exposure.